2014
DOI: 10.1152/japplphysiol.00325.2014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance training on tendon mechanical properties and rapid force production in prepubertal children

Abstract: Children develop lower levels of muscle force, and at slower rates, than adults. Although strength training in children is expected to reduce this differential, a synchronous adaptation in the tendon must be achieved to ensure forces continue to be transmitted to the skeleton with efficiency while minimizing the risk of strain-related tendon injury. We hypothesized that resistance training (RT) would alter tendon mechanical properties in children concomitantly with changes in force production characteristics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
2
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 64 publications
4
80
2
7
Order By: Relevance
“…However, despite correlations being observed between tendon stiffness (or changes with exercise training) and electromechanical delay (or its change with training) (Waugh et al 2013(Waugh et al , 2014, this effect has not been shown explicitly. Reductions in tendon stiffness are also thought to affect the rate of force development (Bojsen-Møller et al 2005;Waugh et al 2013).…”
Section: Diminished Electromechanical Couplingmentioning
confidence: 95%
See 2 more Smart Citations
“…However, despite correlations being observed between tendon stiffness (or changes with exercise training) and electromechanical delay (or its change with training) (Waugh et al 2013(Waugh et al , 2014, this effect has not been shown explicitly. Reductions in tendon stiffness are also thought to affect the rate of force development (Bojsen-Møller et al 2005;Waugh et al 2013).…”
Section: Diminished Electromechanical Couplingmentioning
confidence: 95%
“…Changes in tendon stiffness also speculatively influence electromechanical delay (Cresswell et al 1995;Waugh et al 2013Waugh et al , 2014 and thus reduce the rate of force production. However, despite correlations being observed between tendon stiffness (or changes with exercise training) and electromechanical delay (or its change with training) (Waugh et al 2013(Waugh et al , 2014, this effect has not been shown explicitly.…”
Section: Diminished Electromechanical Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Waugh et al 18 evaluated the calcaneal tendon of children subjected to resisted plantar flexion exercises, noting that there were changes in mechanical properties of tendons, with 29% increase of rigidity. Again it should be noted that in this study we used animals with healthy central nervous system, and therefore with normal muscle adaptive capacities.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that Achilles tendon stiffness significantly increased (29%) after a 10-week resistance training in pre-pubertal children (3,4)) whereas throughout the same study no change in tendon CSA has been mentioned (4). Therefore, the immature human Achilles tendons respond to short-term resistance training similarly to mature tendons (5).…”
Section: Introductionmentioning
confidence: 91%